Plan de exportación de concentrado de maracuyá ecuatoriano al mercado japonés. Correspondencia a la línea de investigación: política económica internacional y comercio justo - Ayala Tumbaco, Amada del Consuelo (2013)
This thesis will reveal the economic demand and financial feasibility to market the Ecuadorian passion fruit concentrate with an attractive cost for new investors in Japan, was developed export plan that analyzes the role of the company, its ability to production and export product, revealing the requirements, international standards and trade agreements that allow successful entry into the Japanese market this product. The passion fruit is grown mainly in the coastal region, and marginally in the Sierra, with a total of 50 cantons, for the year 2010; the total was 9,342 hectares nationwide, with a production of 63,749 metric tons, according to the estimates of the Ministry of Agriculture and Livestock. This proposal was made as a result of a study also discloses the production and marketing of Ecuadorian passion fruit concentrate and trends of the Japanese consumer. During this research was done public company visits related to export and promotion of passion fruit. We also identify trade agreements that make viable revenue product to Japan market, trends and preferences of Japanese consumers. The export plan involves the implementation of strategies and variable analysis, to define the costs that impact is determined that sales of passion fruit concentrate results in a TIR 150%, which would capture the attention of any investor who wants to venture into a project of this nature.